Using PMHS for Catalytic Hydrosilylation with Dimeric Iron Complexes Featuring Mesoionic Carbene Ligands - Stroek, Wowa; Rowlinson, Nathalie A.V.; Keilwerth, Martin; Pividori, Daniel Maximilian; Meyer, Karsten; Albrecht, Martin (Organometallics, 2024)
While the reduction of unsaturated bonds is well established by catalytic hydrogenation reactions using H2, alternative approaches are appealing for environmental and safety reasons. One of these methods is the catalytic hydrosilylation reaction, which becomes environmentally very friendly when using polymethylhydrosiloxane (PMHS), a waste product from the silicon industry, as a hydrosilylation agent. Here, we report the synthesis and catalytic activity of a range of iron triazolylidene complexes for the hydrosilylation of carbonyls using PMHS with unprecedented turnover numbers up to 72,000. Various functional groups on the substrate aromatic ring are tolerated, including CN, Br, OMe, and NMe2 substituents. The hydrosilylation is not restricted to benzylic ketones and aldehydes, esters, and amides are also converted. Rather remarkable for hydrosilylation, ketones are converted faster than aldehydes. Intermolecular competition experiments suggest that the active catalyst is formed by the coordination of a ketone, which rationalizes the origin of this untypical substrate reactivity trend.
CRIS-Team Scopus Importer:2024-06-28